Conductive Electrospun Nanofibers in The Electrochemical Sensor for Determination of Idarubicin - Hamed Khorami; Mahsa Abbasi; Sepideh Geravand; Faeze Abbasi; Elham Arkan (Helium: Journal of Science and Applied Chemistry, 2024)
The study reports the manufacturing of innovative electrochemical sensors using iron oxide ceramic nanofibers  (Fe₃O₄ and Fe₂O₃) and polyether sulfone nanofibers (PES) to detect idarubicin in blood with sensitive and selective detection. The hybrid nanofiber matrix offers high surface area, excellent conductivity, and synergistic electrocatalytic properties, ideal for detecting idauricin in complex biological matrices. The sensor exhibits a wide linear detection range and remarkable sensitivity. The detection limit was suitable, indicating its ability to detect idarubicin at subclinical concentrations. The device showed excellent selectivity and minimal interference from biological analytes, ensuring reliable performance in blood samples. Repeated experiments measured a relative standard deviation (RSD) of 1.7%, while the repeatability of the independently manufactured sensor showed an RSD of 1.7%, demonstrating the robustness of the manufacturing process. Integrating Fe3O4/Fe2O3 ceramic nanofibers with PES offers a novel approach to overcoming the challenges of electrode and biofouling in blood. The sensor showed high recovery rates in human blood samples, confirming its application in clinical diagnostics. This paper presents a cost-effective and scalable method for constructing hybrid nanofiber electrochemical sensors with high sensitivity, selectivity, and repeatability. The result highlights the potential of Fe3O4/Fe2O3-PES nanofibers as a platform for developing next-generation point-of-care devices for monitoring chemotherapy drugs.